Relationship between Health Resources Support with Exclusive Breastfeeding: An Observational Analytic Study - S K M Misdayanti, - (International Research Organization for Life & Health Sciences (IROLHS), 2016)
Background: Breastfeeding and exclusive breastfeeding for 2 years is highly recommended as an intervention to decrease the neonatal mortality, infant, child, and also as the basis for the development and growth of children. This is supported by UNICEF, the World Health Organization, and the American Academy of Pediatrics recommends exclusive breastfeeding until the baby is 6 months old. Materials and Methods: The study was observational analytic study using a case–control approach. The respondents were mothers with infants aged 6-12 Bulan. Cases population was mothers who did not work exclusively breastfed, while population control is the mother who successfully exclusive breastfeeding. Results: The correlation analysis showed that support health workers associated with the cessation of breastfeeding in the working area Puskesmas Lameuru with P = 0.014 (P > 0.05) and odds ratio value (OR: 3.088; 95% CI: 1.240-7.692). Conclusion: The mothers get good support from health resources information support, instrumental support, emotional support, and the support of the award and will make the mother more optimistic in the face of difficulties in breastfeeding. The Astronomical Society of India (ASI) formed a support group (KP-ASI) for pregnant women and mothers with babies under 2 years of age are facilitated by motivators, counselors, midwives, nutrition, and trained workers are one of the real forms of the support of health workers.